Effect of Referring Expression on Antecedent-Grouping Choice in Plural Reference Resolution. Issue 2 (17th February 2018) - Çokal, Derya; Sturt, Patrick
ABSTRACT: This article reports one eye-tracking and one sentence-completion experiment, examining the antecedent preferences for plural anaphora they and demonstrative these . Our results show that the antecedent-grouping preference depends on type of referring expressions: specifically, the preference for they is to refer to a smaller paired group within the context, whereas the preference for these is to refer to a larger (maximal) grouping. This points to limitations regarding the application of the Closure Strategy (Koh & Clifton, 2002), which would have predicted a more general maximal-grouping preference for the contexts investigated here. Previous findings comparing singular pronouns with demonstratives ( it and this ) show that, relative to pronouns, demonstratives prefer more inferentially complex antecedents. With this in mind, the current results could be explained if the preference for the demonstrative was to refer to a more complex referent than that of the pronoun.